The Ambiguous Boeslunde Figure - Borake, Trine Louise (Danish Journal of Archaeology, 2021)
This article presents a unique female figure found in Boeslunde, Zealand, Denmark. It stands at just 1.5 cm and is made of gilded silver with remarkably refined details. The date of the figure is discussed based on details of her garments, accessories, and hairstyle and she is compared to other archaeological representations and finds. Based on these criteria, a dating to the Late Iron Age/Early Viking Age is proposed. Her function is likewise discussed. By means of an examination of parallel finds, the figure’s function as a gaming piece or garment accessory has been ruled out. It is argued that she functioned as an amulet and her features are evaluated and discussed. Contemplating the figure from a ritual perspective, her necklace appears to be a significant attribute, an observation which has great implications for other representations such as the Odin-from-Lejre figure. It is, further considered whether her necklace is a representation of Freyja´s Brisingamen, and the little figure thus a depiction of Freyja, herself. Lastly, the intentionally differentiated shape and size of her eyes and their symbolic meaning is evaluated, and parallels are examined and discussed.